Implementasi Lisensi Wajib TRIPs Agreement dalam Produk Farmasi di Negara Swedia - Luqman Hakim (Jurnal Hukum Lex Generalis, 2023)
Patent protection on types of drugs before and after the TRIPs agreement has become a hot topic of discussion regarding drug patents and the general public's access to medicines. Drugs are available, but the quality standards are not good because they are counterfeited or produced without credible quality control so they are dangerous. The implementation of mandatory TRIPs licensing of medicines in Sweden is carried out in accordance with the Swedish State Patent Law (Sweden Patentkungörelsen 1967). Regarding the mandatory licensing of the TRIPs Agreement by the government in Sweden, it is in accordance with Paragraph 6 of the Doha Declaration on TRIPs Agreement and Public Health, namely, Promote access to medicines for all on the basis of implementation as stated in Article 31 of the TRIPs Agreement. The public hopes that the implementation of patents by the Government on drugs, especially antiretrovirals in Sweden, can facilitate access for people with HIV/AIDS to obtain the needed antiretroviral drugs. In addition, the implementation of compulsory licensing for local producers can be an effective strategy to promote generic drug competition in the pharmaceutical industry.